1977
DOI: 10.1093/jn/107.2.194
|View full text |Cite
|
Sign up to set email alerts
|

Relative Activities of Some Metabolites and Analogs of Cholecalciferol in Stimulation of Tibia Ash Weight in Chicks Otherwise Deprived of Vitamin D

Abstract: Nine metabolites and analogs of cholecalciferol (CC) were tested for ability to increase tibia ash weight in chicks otherwise deprived of vitamin D. All of the compounds promoted bone mineralization in a linear log dose-response relationship. The maximal response obtained for any compound was an approximate doubling in bone ash weight compared to vehicle-treated controls. Relative potencies, based upon the calculated ash weight doubling dose, were as follows: 1 alpha, 25-(OH)2-CC = 1 alpha-OH-CC greater than C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

1980
1980
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…Previous research has shown that 1α-OH D 3 is 4.5 times more active than vitamin D 3 in respect to the BWG of broiler chickens (Soares et al, 1978), 8.6 times in respect to tibia ash increase (Boris et al, 1977), and at least 10 times in terms of mobilizing bone calcium and raising plasma calcium concentrations in Leghorn cockerels (Haussler et al, 1973). Using body weight, plasma Ca, tibia ash weight and percentage, and incidence of rickets as criteria, Edwards et al (2002) reported that the relative biological values of 1α-OH D 3 to vitamin D 3 were 10.08, 9.50, 11.26, 4.48, and 4.50, respectively.…”
Section: Discussionmentioning
confidence: 92%
“…Previous research has shown that 1α-OH D 3 is 4.5 times more active than vitamin D 3 in respect to the BWG of broiler chickens (Soares et al, 1978), 8.6 times in respect to tibia ash increase (Boris et al, 1977), and at least 10 times in terms of mobilizing bone calcium and raising plasma calcium concentrations in Leghorn cockerels (Haussler et al, 1973). Using body weight, plasma Ca, tibia ash weight and percentage, and incidence of rickets as criteria, Edwards et al (2002) reported that the relative biological values of 1α-OH D 3 to vitamin D 3 were 10.08, 9.50, 11.26, 4.48, and 4.50, respectively.…”
Section: Discussionmentioning
confidence: 92%
“…It is generally considered that 1,25(OH)2D3 is the most active form of vitamin D responsible for increasing the absorption of calcium and phosphate from the intestine [9,10], mobilizing these ions from bone [11][12][13][14] and increasing bone mineralization as measured by ash weight [15]. Nonetheless, substantial evidence has been accumulating which strongly suggests that other vitamin D metabolites are required for the full expression of vitamin D activity [16][17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in phosphate levels obtained with the high dose of 25(OH)D3 and a 10 times higher dose of 24,25(OH)2D3 was not related to an increase in the levels of serum calcium, suggesting that the vitamin D metabolites may have a direct role in phosphate metabolism, independent of their effect on the levels of serum calcium. The effects of 24,25(OH)~D3 on the level of serum calcium and phosphate may be significant when it is considered that under normal physiological conditions, in man, 24,25(OH)2D3 has been reported to be found in the serum in 100 times higher concentrations than 1,25(OH)2D3 [15].…”
Section: Discussionmentioning
confidence: 99%
“…1,25(OH) 2 -24-keto-D 3 has been identified as a major metabolite produced by the rat intestine, in vitro and in vivo, establishing C24 oxidation as a key metabolic pathway; this metabolite is the substrate for the subsequent C23 hydroxylation (Napoli et al, 1983a, b). Based on a study performed in chickens (Boris et al, 1977) (Esvelt et al, 1979;Reddy and Tserng, 1989).…”
Section: Vitamin Dmentioning
confidence: 99%